378 Monoclonal Antibody Targeting Connexion 43 Hemichannel Improves Functional Recovery and Reduces Secondary Injury After Traumatic Spinal Cord Injury. (August 2016) - Maknojia, Asif; Sprague, Shane M.; Riquelme, Manuel; Gu, Sumin; Reed, Pamela; Bartanusz, Viktor; Jiang, Jean; Sayre, Naomi
Abstract : INTRODUCTION: Connexion 43, a gap junction protein, is expressed abundantly in the central nervous system (CNS) and has been implicated in propagating secondary injury in the CNS. In this report we use a monoclonal antibody against Cx43 hemichannel to study the effects of regulating Cx43 activity during spinal cord injury (SCI) in a mouse model. METHODS: C57BL/6 male mice underwent T10 to 12 laminectomies and were injured using a impactor at a speed of 3 m/s, displacement of 2 mm and dwelling time of 1500 ms. Mice were randomly assigned to C x 43+ SCI (n = 5), Igg+ SCI (n = 3), or vehicle + SCI (n = 1) group and drugs were administered 30 minutes after injury. The Basso Mouse Scale (BMS) and rotarod testing was used to track functional recovery up to 6 weeks after injury. In addition, immunohistochemistry was performed to assess for the inflammatory response. RESULTS: Blocking of Cx43 promoted faster recovery of locomotor function after SCI. At 6 weeks Cx43 ab treated animals achieved a mean BMS score of 7.8 (SD 1.68) compared with 1.3 (SD 1.04) in the Igg group ( P < .01). Cx43 ab treated mice regained 80% of their pre-SCI ability to spend time on accelerating rotarod as opposed to only 25% in the control group ( P < .05). Immunohistochemical staining for astrogliotic scarring showed a 6.3-fold increase in GFAP signal in Igg-treated mice compared with 1.3 in the Cx43-treated animals at day 14 ( P = .065). These trends persisted at day 56 ( P < .01). Neun staining for neurons showed a 25% decrease in Neun signal in Igg-treated mice compared with 2% in Cx43-treated mice ( P < .05) at day 14. CONCLUSION: Mice treated with Cx43 monoclonal antibody show improved functional recovery and neuronal survival and decreased astrogliosis compared with Igg-treated mice. Combined, these results confirm Cx43 hemichannel as a viable therapeutic target for traumatic SCI.